PENGARUH PENAMBAHAN TEPUNG DAUN PEPAYA (Carica papaya L) DALAM RANSUM TERHADAP PERSENTASE KARKAS BAGIAN DADA DAN PAHA ITIK MANILA - Herdi Herdianto; Soegeng Herijanto; Sulistyaningtyas; Yanita Viastika (MEDIA PETERNAKAN, 2025)
The study entitled "The Effect of Adding Papaya Leaf Flour (Carica Papaya L) in Feed on the Percentage of Breast and Thigh Carcas of Manila Ducks" was to determine the effect of adding papaya leaf flour to feed on the percentage of breast and thigh carcas of Manila ducks. This study used 40 five-week-old Manila ducks. The experimental design used was a Completely Randomized Design (CRD) One-Way Pattern with four types of treatments, namely PO (addition of 0% papaya leaf flour), P1 (addition of 2% papaya leaf flour), P2 (addition of 4% papaya leaf flour), and P3 (addition of 6% papaya leaf flour). Each treatment consisted of five replications. The parameters observed included the percentage of breast and thigh carcas of Manila ducks. The results showed that the average percentage of breast carcas of Manila ducks treated with P0; P1; P2; and P3 were 26.66; 28.11; 28.56; and 27.23 % respectively. The average percentage of thigh meat of Manila ducks treated with P0; P1; P2; and P3 was 25.82; 26.07; 27.36; and 26.19%, respectively. The highest percentage of breast and thigh carcas were obtained from Manila ducks treated with four percent papaya leaf flour (P2).